Associations between Japanese calligraphy practice and sleep quality in community-dwelling older adults: A cross-sectional Study - Georg von Fingerhut; Keitaro Makino; Osamu Katayama; Ryo Yamaguchi; Daiki Yamagiwa; Jessica K. Bone; Hiroyuki Shimada (Sleep Medicine: X, 2024)
Background: Sleep disturbances, such as insomnia, are common among the elderly population and have been associated with negative health outcomes. Japanese calligraphy is a traditional art practice previously associated with various health benefits, such as stress reduction and improved cognitive function; however, its association with sleep quality has not been fully explored. Methods: This cross-sectional study included 21,207 subjects with basic attributes, health status, depressive symptoms, artistic practices, and sleep habits. Individuals who satisfied the chronic insomnia criteria were categorized into the following subtypes: sleep onset latency (SOL) insomnia, early morning awakening (EMA) insomnia, and wake after sleep offset (WASF) insomnia. The t-test, chi-square test, and logistic regression analysis were used to determine the association between Japanese calligraphy practice and sleep quality. Results: In this study, 17,597 elderly Japanese individuals were included, among whom 13.7 % practiced Japanese calligraphy. Regarding sleep characteristics, 32.0 % had chronic insomnia, 13.1 % had SOL insomnia, 9.1 % had EMA insomnia, and 14.2 % had WASF insomnia. Japanese calligraphy practice was associated with lower rates of chronic insomnia (odds ratio [OR] = 0.85, 95 % confidence interval (CI) = 0.76–0.95), including SOL insomnia (OR = 0.84, 95 % CI = 0.71–0.98), and EMA insomnia (OR = 0.80, 95 % CI = 0.66–0.97) but had no significant association with WASF insomnia. Conclusions: This study suggests that Japanese calligraphy practice is associated with lower odds of insomnia, particularly SOL and EMA insomnia. Calligraphy may be an effective nonpharmacological intervention for insomnia and poor sleep quality among elderly Japanese individuals.